The efficacy of karate (lambdacyhalothrin) in controlling heloidogyne incognita (kofoid and white) on soybeans (glycine max. L. Merril.) (1997)
The nematicidal properties of a synthetic pyrethriod (Karate) was investigated. In laboratory experiments, Karate at different concentrations (4,000ppm, 6,000ppm and 8,000pm against Meloidogyne incognita (kofoid and white) prevented egg- hatch and accentuated the death of the infective second stage juveniles. In green-house experiments, as little as 4,000ppm of Karate reduced both the number of galls and the population of juveniles in soils when compare with the Control plants. However, Karate applied as soil-drench resulted in wilting of plants at all concentrations